Grazing reserves and development of traditional pastoralism in Nigeria: progress and prospects (1999)
The Nigerian beef industry is controlled by pastoralists for whom production strategies are primarily for stock survival rather than increased off-take. Their production system is in the traditional (extensive migratory) phase of development, which needs to be modernized (intensified) to bridge the increasing gap between supply and demand for beef in Nigeria while sustaining the pastoral lifestyle of the producers. In this paper, the most sustained effort at development of pastoralism - the grazing reserve scheme - is examined for its effectiveness Using the Dobi Grazing Reserve in Niger State. Nigeria as study area, its progress towards the settlement and economic development of pastoralism is evaluated. From the result, an unprecedented voluntary settlement of pastoralist and marginally improved production parameters are recorded. Possession of land rights, grazing security, presence of water and grazing resources, and the deliberate policy of encouraging transhumance activity out of the reserve during the dry season, were factors responsible for the voluntary settlement. The need for stricter stock control measures, provision of extension/veterinary services and socio-economic infrastructure and a greater involvement of settlers in the funding and administration of the reserve are highlighted as conditions for sustaining the programme.